Effects of endurance training on the breathing pattern of professional cyclists - Lucia, A.; Hoyos, J.; Pardo, J.; Chicharro, J. L. (2001)
The aim of this longitudinal study was to clarify the changes induced by endurance training on the breathing pattern of 13 professional cyclists (age+/-SD: 24+/-2 years; VO(2 max) approximately 75 ml x kg(-1) x min(-1)) during the three periods (rest, precompetition, and competition) of a sports season. Both the volume and the intensity of training were quantified during these periods. In each session (corresponding to each of the three periods) all subjects performed (1) a pulmonary function test (to measure forced vital capacity [FVC], peak expiratory flow [PEF], and maximal voluntary ventilation [MVV]), and (2) a ramp test until exhaustion on a cycle ergometer (workload increases of 25 W x min(-1)). The following variables were recorded every 100 W until the end of the tests: pulmonary ventilation (VE, in l x min(-1) BTPS), tidal volume (VT, inl BTPS), breathing frequency (f(b), in breaths x min(-1)), ventilatory equivalents for oxygen (VE x VO(2)(-1)) and carbon dioxide (VE x VCO(2)(-1)), inspiratory (TI) and expiratory (TE) times (s), ratio of TI to total respiratory duration or inspiratory "duty cycle" (TI/TTOT, and mean inspiratory flow rate (VT)/TI), in l x s(-1)). The results showed no changes in any of these variables (p>0.05) between the three periods of study, despite significant changes in training loads (i.e., increases in the volume and/or intensity of training throughout the season). These findings suggest that endurance conditioning does not alter the breathing pattern of professional cyclists during an incremental exercise test. Jpn J Physiol 2001 Apr;51(2):133-41